2012
DOI: 10.1007/s00395-012-0264-6
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of voltage-dependent K+ and Ca2+ channels to coronary pressure-flow autoregulation

Abstract: The mechanisms responsible for coronary pressure-flow autoregulation, a critical physiologic phenomenon that maintains coronary blood flow relatively constant in the presence of changes in perfusion pressure, remain poorly understood. This investigation tested the hypothesis that voltage-sensitive K+ (KV) and Ca2+ (CaV1.2) channels play a critical role in coronary pressure-flow autoregulation in vivo. Experiments were performed in open-chest, anesthetized Ossabaw swine during step changes in coronary perfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 68 publications
3
43
0
Order By: Relevance
“…These data, along with concurrent evidence that PVAT-derived factors significantly impair coronary vasodilation of H 2 O 2 -sensitive K + channels 23 , indicate that the effects of coronary PVAT are related not only to inherent alterations in coronary PVAT expression profiles but also to underlying mechanistic differences in obese coronary artery smooth muscle cells. This hypothesis is supported by earlier studies from our laboratory and others which have demonstrated that obesity decreases the functional expression of coronary K + channels 99-103 and increases coronary Ca V 1.2 channel current, expression, and contraction 51, 52, 104 .…”
Section: Pathways Influenced By Coronary Pvatsupporting
confidence: 80%
See 1 more Smart Citation
“…These data, along with concurrent evidence that PVAT-derived factors significantly impair coronary vasodilation of H 2 O 2 -sensitive K + channels 23 , indicate that the effects of coronary PVAT are related not only to inherent alterations in coronary PVAT expression profiles but also to underlying mechanistic differences in obese coronary artery smooth muscle cells. This hypothesis is supported by earlier studies from our laboratory and others which have demonstrated that obesity decreases the functional expression of coronary K + channels 99-103 and increases coronary Ca V 1.2 channel current, expression, and contraction 51, 52, 104 .…”
Section: Pathways Influenced By Coronary Pvatsupporting
confidence: 80%
“…Furthermore, the constricting effect of coronary PVAT was markedly exaggerated in endothelium intact and denuded coronary arteries from obese swine. Additional findings support that these enhanced effects are associated with substantial alterations in the protein expression of obese coronary PVAT 23, 24 and with inherent differences in the phenotype of obese smooth muscle cells 51, 52 . Taken together, these findings indicate that factors derived from coronary PVAT can act to impair endothelial-dependent dilation and potentiate contractions of coronary vascular smooth muscle, especially in the setting of obesity.…”
Section: Vascular Effects Of Peripheral Vs Coronary Pvatmentioning
confidence: 61%
“…10,11 In contrast, 4-aminopyridine (4-AP)-sensitive K V channels mediate dilation to H 2 O 2 in canine coronary arteries, 12 rat coronary and mesenteric arteries, 12, 13 and porcine coronary resistance arteries. 14 Using coronary arterioles from CAD subjects, we found that H 2 O 2 opens smooth muscle BK Ca channels to elicit smooth muscle hyperpolarization and relaxation. 6, 7 The mechanisms of dilation by H 2 O 2 in subjects without CAD (non-CAD) versus those with CAD, as well as the functional consequences, remain unknown, but there is evidence that BK Ca and K V constitute two major K + currents in VSMCs isolated from non-CAD human arteries.…”
Section: Introductionmentioning
confidence: 92%
“…Although multiple types of K + channels are expressed in coronary vascular smooth muscle, voltage-dependent K + (K V ) channels appear to play a predominant role, as relatively nonselective inhibition of these channels with 4-aminopyrindine (4-AP) reduces baseline coronary blood flow and inhibits local metabolic and ischemic vasodilation [3, 4, 9]. The precise K V channel subtypes involved have not, however, been clearly defined.…”
Section: Introductionmentioning
confidence: 99%